A Case Report of Fatal Necrotizing Encephalitis and Acute HBV Infection: Coincidence or Comorbidity? - Krzysztofiak, Andrzej; Bozzola, Elena; Russo, Cristina; De Vito, Rita; Nobili, Valerio; Villani, Alberto (Journal of Pediatric Infectious Diseases, 2019)
We report the first fatal pediatric case of encephalitis associated with hepatitis B virus (HBV) infection. A Caucasian, previously healthy, and vaccinated 7-year-old girl was evaluated at our hospital for fever, vomiting, tremors, and loss of consciousness. At admission, she underwent brain computed tomographic scan, electroencephalogram, lumbar puncture, and blood examination. In 12 hours, her clinical condition deteriorated and the patient entered coma and died. A laboratory error was useful to reach a predeath diagnosis, showing HBV–DNA on blood. Autopsy confirmed HBV–PCR DNA in brain, lymphnodes, lungs, liver, and spleen. We generally do not search HBV–DNA in organic fluid of Italian children with encephalitis, as they are currently all vaccinated. Consequently, as a teaching lesson, we would suggest not to take anything obvious.
Keywords: encephalitis; hepatitis B virus; children